Unique spatially and temporary-regulated/sex-specific expression of a long ncRNA, Nb-1, suggesting its pleiotropic functions associated with honey bee lifecycle - Hiroto Tadano; Hiroki Kohno; Hideaki Takeuchi; Takeo Kubo (Scientific Reports, 2024)
Abstract Honey bees are social insects, and each colony member has unique morphological and physiological traits associated with their social tasks. Previously, we identified a long non-coding RNA from honey bees, termed Nb-1, whose expression in the brain decreases associated with the age-polyethism of workers and is detected in some neurosecretory cells and octopaminergic neurons, suggesting its role in the regulation of worker labor transition. Herein, we investigated its spatially and temporary-regulated/sex-specific expression. Nb-1 was expressed as an abundant maternal RNA during oogenesis and embryogenesis in both sexes. In addition, Nb-1 was expressed preferentially in the proliferating neuroblasts of the mushroom bodies (a higher-order center of the insect brain) in the pupal brains, suggesting its role in embryogenesis and mushroom body development. On the contrary, Nb-1 was expressed in a drone-specific manner in the pupal and adult retina, suggesting its role in the drone visual development and/or sense. Subcellular localization of Nb-1 in the brain during development differed depending on the cell type. Considering that Nb-1 is conserved only in Apidae, our findings suggest that Nb-1 potentially has pleiotropic functions in the expression of multiple developmental, behavioral, and physiological traits, which are closely associated with the honey bee lifecycle.